Nationalism Edition Interactive Textbook: Solution to Enhance National Insight of Migrant Worker’s Children in Malaysia - Nabilah, Jennie; Adzronnida, Tsabitah Nuril; Alifia, Putri Ismukhanah Ayu (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
The effort to preserve national identity has become an increasingly difficult challenge for Indonesian Migrant Worker children in Malaysia, who are often separated from Indonesian culture and educational systems. Growing up in a multicultural environment, these children require resources that can strengthen their sense of nationalism to prevent the erosion of Indonesian cultural identity. This study aims to address this need by developing an interactive textbook on nationalism to enhance the national awareness of Indonesian Migrant Worker children at ICC Muar, Johor. Using a Research and Development (R&D) approach with quantitative assessments through pretests and posttests, this study shows a significant improvement in students' national awareness, with a mean score difference of 29.0, a t-statistic value of 6.692 (p < 0.001), and a Cohen’s d of 2.116. These results indicate that the interactive textbook is effective in reinforcing national identity. This study recommends the use of interactive textbooks in non-formal education as an effort to safeguard national identity among IMWs children growing up in multicultural settings.